Gender, Sexuality, and Religion: A Critical Integrative Review and Agenda for Future Research. Issue 2 (27th January 2022) - Schnabel, Landon; Abdelhadi, Eman; Ally Zaslavsky, Katherine; Ho, Jacqueline S.; Torres‐Beltran, Angie
Abstract: This article sets forth a critical integrative review of the study of gender, sexuality, and religion. Treating religion as a cause, an effect, and an intermediary factor in relation to gender and sexuality, it draws on and synthesizes multiple theoretical approaches, including gender and queer lenses on religion, cultural analysis, and intersectionality. The article is structured around 10 big‐picture questions about gender, sexuality, and religion and argues that gender and sexuality are a key symbolic boundary and cultural divide in religious and political life in the United States and around the world. It concludes with an agenda for future research.